Analysis of the causes of compulsive smoking behavior among adolescents in South Sumatra - Aditya Agal Rivansyah; Anggi Triyani; Minarsi Minarsi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This research aims to explore the causes and reasons behind smoking behavior in adolescents, which has become a compulsive behavior. The research method used is qualitative, employing a descriptive phenomenological approach. The findings reveal two factors contributing to the compulsive smoking behavior in adolescents, categorized into five aspects: knowledge about cigarettes, attitudes, the influence of cigarette advertisements, peer pressure, and family. It can be concluded that smoking behavior in adolescents is influenced by various factors that increase the prevalence of smoking and lead to compulsive behavior. In this study, peer influence has a significant impact on smoking behavior among adolescents